DAYA TARIK WISATA ALAM NGALAU INDAH DI KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Santri Yulia; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The natural attractions of an area are influenced by the quality of the landscape, the authenticity of nature and the beauty of the panorama. Ngalau Indah is a tourist attraction on the hill of Simarajo which is a protected green forest area that has cool air and beautiful scenery. Viewed from the last 5 (five) years the number of tourist visits to Ngalau Indah Tourism Object is unstable. As a reference in optimizing the management to know how the assessment of tourists to tourist attraction , so that later can increase the number of visitors to the attraction itself. The purpose of this study to determine the attractiveness of natural attractions Ngalau Indah and To know the management effort in attracting tourists to visit Ngalau Indah tourist attraction. This research is done Tourism Object Ngalau Indah, precisely in Kelurahan Pakan Sinayan Payakumbuh West Payakumbuh District. This research uses qualitative method with descriptive approach by collecting data and information in field and explain in the form of description without testing hypothesis or make prediction. Data analysis techniques obtained by field observation, interviews and documentation and then in if or in the analysis to achieve the ultimate goal. Based on the research results of tourist attraction in the Tourism Object Ngalau Indah is in the category of